Changing chemistry of particulate manganese in the near- and far-field hydrothermal plumes from 15°S East Pacific Rise and its influence on metal scavenging. (1st May 2021) - Lee, Jong-Mi; Lam, Phoebe J.; Vivancos, Sebastian M.; Pavia, Frank J.; Anderson, Robert F.; Lu, Yanbin; Cheng, Hai; Zhang, Pu; Edwards, R. Lawrence; Xiang, Yang; Webb, Samuel M.
Abstract: Dissolved Mn(II) in the hydrothermal plume is known to be microbially oxidized to form Mn(III/IV) oxides, and the Mn oxides scavenge other trace elements in seawater. In the GEOTRACES GP16 cruise, dissolved Mn (dMn) and particulate Mn (pMn) were found to be transported over 4000 km westwards from the Southern Eastern Pacific Rise. Previous studies in this plume showed different removal rates of dMn and pMn as well as pMn size distribution between the near-field (<80 km from the ridge axis) and far-field (>80 km) plumes. In order to understand Mn cycling in these plumes, spatial distribution, oxidation states, and mineral structures of Mn in small size fraction (SSF; 0.8–51 μm) and large size fraction (LSF; >51 μm) particles from the near-field and far-field plumes were examined using micro X-ray fluorescence spectrometry (μ-XRF), X-ray absorption near-edge structure spectroscopy (XANES), chemical species mapping, and extended X-ray absorption fine-structure spectroscopy (EXAFS). In the near-field plume, pMn in the SSF is dominated by oxidized Mn with Mn(III) fractions of ∼30%. They are a mixture of δ-MnO2 and triclinic birnessites that is known to be formed as a result of autocatalytic Mn(II) oxidation at the surface of freshly-formed δ-MnO2, suggesting that both microbial and autocatalytic Mn oxidation occur in the near-field plume. The LSF pMn in the near-field plume is also oxidized and often found in large aggregates several hundreds of μm in size. These aggregates settle out in the near-field and during transport, and are not found in the far-field plume. In the far-field plume where Mn oxides are not newly formed, pMn in the SSF is oxidized, but their Mn(III) fractions are smaller than in the near-field pMn. Unlike the SSF, the far-field plume LSF pMn is dominated by reduced Mn, implying very slow aggregation of pMn in the far-field plume. The different characteristics of pMn between the near-field and far-field plumes affect its scavenging of other trace elements. In the near-field plume, Co, Mo, 231 Pa are associated with pMn, but not in the far-field plume. 231 Pa is adsorbed to pFe rather than pMn in the far-field plume, and Pb is adsorbed to pFe in the entire plume. The result shows that freshly-formed Mn oxides in the near-field plume have higher scavenging capacity than the far-field plume pMn. Our findings suggest that the mineralogical age of Mn oxides may be an important parameter that controls the scavenging of many other trace elements and isotopes.